2006
DOI: 10.1124/mol.106.029629
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Antagonist Fulvestrant (ICI 182,780) Inhibits the Anti-Inflammatory Effect of Glucocorticoids

Abstract: The glucocorticoid receptor (GR) and estrogen receptor (ER) play important roles in both physiological and pathological conditions involving cell growth and differentiation, lipolysis, control of glucose metabolism, immunity, and inflammation. In fact, recent studies suggest that 17␤-estradiol, like glucocorticoids, may also have anti-inflammatory properties, even if the molecular mechanisms responsible for these activities have not yet been completely clarified. The present study was designed to gain a better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
(63 reference statements)
1
18
0
1
Order By: Relevance
“…Recently, the same group has demonstrated that ERa can drive pro-inflammatory cytokine repression caused by glucocorticoids (Cvoro et al, 2011). Accordingly, in vivo addition of estrogen receptor antagonist ICI182780 inhibits the anti-inflammatory effect of glucocorticoids in mice (Cuzzocrea et al, 2007). In line with the above evidence, we have found that addition of glucocorticoids caused an expected decrease in pro-inflammatory cytokine levels through ERa.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, the same group has demonstrated that ERa can drive pro-inflammatory cytokine repression caused by glucocorticoids (Cvoro et al, 2011). Accordingly, in vivo addition of estrogen receptor antagonist ICI182780 inhibits the anti-inflammatory effect of glucocorticoids in mice (Cuzzocrea et al, 2007). In line with the above evidence, we have found that addition of glucocorticoids caused an expected decrease in pro-inflammatory cytokine levels through ERa.…”
Section: Discussionsupporting
confidence: 76%
“…Despite the findings that both GR and ER repress proinflammatory cytokine genes, little is known about the potential cross talk between GR and ER. However, in an experimental lung inflammation rat model, the ER antagonist ICI 182780 (ICI) blocked the anti-inflammatory effects of glucocorticoids (19). This finding suggests that when ER is bound to an antagonist, it can cross talk with GR to block its anti-inflammatory action, but mechanism for this effect is unknown.…”
mentioning
confidence: 93%
“…Multiple mechanisms are involved in GC-mediated anti-inflammatory activity in addition to direct GR/NF-B interaction, such as GC-induced up-regulation of IB and glucocorticoid-induced leucine zipper (GILZ), two proteins able to bind and inhibit NF-B activation (Ray and Prefontaine, 1994;Auphan et al, 1995;Scheinman et al, 1995;Cannarile et al, 2006;Di Marco et al, 2007). After NF-B inhibition, a number of inflammatory parameters are blocked, including cytokine production, cell migration, COX-2 and inducible nitric-oxide synthase (iNOS) activation, and tissue damage (Barnes and Karin, 1997;Yamamoto and Gaynor, 2001;Gilroy et al, 2004;Cuzzocrea et al, 2007).…”
mentioning
confidence: 99%